The activity of foreign versus locally-owned companies: Financial perspective - Magdalena Jasiniak (e-Finanse: Financial Internet Quarterly, 2011)
The aim of this paper is to compare the financial effects of domestic and foreign companies activities on the basis of two randomly chosen enterprises. It is argued that foreign companies are the carriers of modern technologies what have the influence on financial results obtained by them. However, their successes cannot be attributed only to better innovativeness but also to better use of borrowed capital. Higher proneness to risk resulting from financing the company activities from external sources in the long-term perspective may bring the company higher profitability and, in consequence, contribute to faster development of the enterprise.
Keywords: G32; 330; foreign companies activities; innovativeness; financial analysis